2021
DOI: 10.54259/ijba.v1i2.76
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Mempengaruhi Auditor Switching Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia

Abstract: Penelitian ini bertujuan untuk mengetahui Faktor-Faktor Yang Mempengaruhi Auditor switching  Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia. Penelitian ini menggunakan pendekatan deskriptif kuantitatif, bertujuan untuk mengetahui hubungan antara dua variabel atau lebih. Populasi penelitian ini adalah Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia yaitu sebanyak 54 perusahaan. Sampel penelitian ini sebanyak 30 perusahaan dikali 3 tahun sehingga sampel pada penelitian ini yaitu s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
1
4
1
1
Order By: Relevance
“…The research by Manto & Manda (2018) and Zarefar et al, (2019) show that financial distress affects auditor switching. The results of this study were also reinforced by research conducted by (Herawaty & Ovami, 2021) which found that companies that experienced financial distress will increase the client company's tendency to perform auditor switching. In contrast, research conducted by (Putri &Nursiam, 2021) and(Sambo, 2022) shows that financial distress has no effect on auditor switching.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…The research by Manto & Manda (2018) and Zarefar et al, (2019) show that financial distress affects auditor switching. The results of this study were also reinforced by research conducted by (Herawaty & Ovami, 2021) which found that companies that experienced financial distress will increase the client company's tendency to perform auditor switching. In contrast, research conducted by (Putri &Nursiam, 2021) and(Sambo, 2022) shows that financial distress has no effect on auditor switching.…”
Section: Introductionsupporting
confidence: 59%
“…The replacement of auditors is expected to enhance the company's reputation and foster increased trust among stakeholders (Swandewi & Badera, 2021). This matter is supported by studies conducted by Fenadi (2019) and (Herawaty & Ovami, 2021) which demonstrate that profitability has an influence on auditor switching. These studies show that the greater the profitability, the higher possibility of the client company performing Auditor switching.…”
Section: Introductionmentioning
confidence: 59%
“…Large companies can also change auditors before the specified time, assuming other than an unqualified opinion (Safriliana et al 2020). Results of research conducted by Herawaty & Ovami (2021) show that the size of the company has a positive effect on switching auditors. This shows that the larger the size of the company, the company performs auditor switching.…”
Section: B the Effect Of Company Size On Switching Auditorsmentioning
confidence: 99%
“…Several studies support that audit opinions influence the existence of switching auditors, including those carried out by (Handoko & Haryanto, (2019); (Qomari & Suryandari, 2019);{Formatting Citation}; (Saaydah, 2021). While according to Andreas & Savitri (2019); Swandewi & Badera (2021); Herawaty & Ovami (2021); Darmayanti et al (2021) demonstrate that the audit opinion does not influence the switching auditor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation